Evaluation of standard 12-lead electrocardiography performed preoperatively in the Department of Oral and Maxillofacial Surgery, Kanto Rosai Hospital - Ohashi, Mizuki; Masuda, Chieko; Sumimoto, Wakako; Nakajima, Hiroshi; Shishido, Kotaro; Okada, Toshie; Misaki, Toru; Nakamichi, Yuka (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 2008)
In recent years, 12-lead electrocardiography (ECG) with automatic analysis function is used in many hospitals for medical evaluation and treatment. In general hospitals, the proportion of patients with disease is higher than that in dental hospitals. Many patients require surgery in our department of oral and maxillofacial surgery. Operations in patients with cardiovascular diseases have a particularly high risk of complications. We preoperatively performed standard 12-lead ECG using a CARDIOPRO-FCP-4266 electrocardiograph equipped with automatic analysis function (Fukuda Denshi) in 55 dental patients (28 males and 27 females, average age 63.4) who required local anesthesia and were receiving treatment for cardiovascular diseases or were suspected to have cardiovascular diseases between October 2006 and November 2007. Medical examination by interview showed that 47 patients, had underlying cardiovascular discase. The total number of diseases was 49, with hypertension in 28 patients (49%), angina pectoris in 3 (5%), myocardial infarction in 3 (5%), irregular pulse in 2 (4%), valvular disease in 2 (4%), and others in 11. Eight patients were normal (14%). ECG abnormalities were present in 31 patients (56.4%), including inferior myocardial infarction in 7 patients (9%), latent inferior myocardial infarction in 4 (5%), atrial fibrillation in 4 (5%), complete right bundle-branch block in 4 (5%), mild ST-T abnormalities in 4 (5%), and ST-T abnormalities in 4 (5%), counterclockwise rotation in 4 (5%), negative T waves in 3 (4%), flat T waves in 3 (4%), and others in 16 (21%). The ECG was normal in 24 patients (32%). Four patients (7.3%) who had ECG abnormalities but no apparent disease on medical examination by interview visited cardiologists; 1 of these patients (1.8%) required medical therapy. Because the analytical accuracy of ECG with data analysis function is very high, patients who are unaware of their diseases can be screened. ECG with data analysis function is thus considered very useful for evaluating risks in dentistry.